Determinant Factors Effecting Poverty Among New Converts in Selangor, Malaysia - Fuadah Johari; Kalsom Abd Wahab; Ahmad Fahme Mohd Ali; Muhammad Ridhwan Abd Aziz (Share: Jurnal Ekonomi dan Keuangan Islam, 2015)
The justice in Islam had attracted and opens the hearts of non-muslins to accept Islam. The justice and truthfulness of Islamic teaching attract the human to be part of its through conversion or reconciliation of hearts (Muallaf al-Qulub) and it is one of the zakat recipients mentioned in Al-Qur’an. In Selangor, zakat assistance to the new converts begins from the first day they become Muslims. The new Muslim would be immediately helped with MYR 500.00 monthly allowance for five years until they manage to act in accordance with Allah’s orders and to perform worshipping (Mukallaf). This paper identifies the factors of new converts’ poverty in Selangor, Malaysia using a logistic regression method. A set of survey questionnaires has been used in this research and 80 respondents were randomly selected from Selangor Zakat Centre (SZC) zakat recipient’s list from the New Converts category for nine districts of Selangor in 2013. We estimate the probability of households with specified characteristics to fall below Malaysia’s official poverty line. Results show that education, size, region, income and amount of zakat received significantly reduces the chance of being poor while gender, age, status were not a significant predictor. Thus, these statistical measures have proven the positive role of zakat in reducing poverty among the new converts. The findings have important policy implications for zakat institution and Malaysian government which has pledged to reduce overall poverty rate to 2.8 percent and eradicates hardcore poverty by 2010 under the Ninth Malaysian Plan. ABSTRAK - Keadilan dalam Islam telah menarik perhatian dan membuka hati non-muslim untuk menerima Islam. Keadilan dan kejujuran dalam ajaran Islam menarik banyak untuk masuk dalam Islam (Muallaf al-Qulub) dan mereka menjadi salah satu penerima zakat seperti disebutkan dalam Al Qur'an. Di Selangor, bantuan zakat kepada para muallaf dimulai pada hari pertama mereka menjadi umat Islam. Mualaf tersebut akan diberi uang saku sebesar MYR 500.00 per bulan selama 5 tahun sampai mereka mampu mengelola kehidupannya sesuai dengan perintah Allah dan melaksanakan ibadahnya (Mukallaf). Paper ini mengidentifikasikan faktor-faktor kemiskinan mualaf di Selangor, Malaysia dengan menggunakan metode regresi logistic. Seperangkat kuesioner digunakan untuk penelitian ini dan 80 responden dipilih secara acak dari daftar para penerima zakat Selangor Zakat Centre (SZC) untuk kategori mualaf dari sembilan distrik di Selangor untuk tahun 2013. Kami memperkirakan probabilitas rumah tangga rumah tangga dengan karakteristik dimaksud mengalami penurunan di bawah angka kemiskinan resmi Malaysia. Hasil menunjukkan bahwa pendidikan, ukuran, wilayah, pendapatan dan jumlah zakat yang diterima secara signifikan mengurangi kemiskinan sementara faktor gender, umur, dan status bukanlah faktor yang signifikan. Oleh karena itu, hasil perhitungan statistik membuktikan bahwa zakat berperan positif dalam mengurangi kemiskinan para mualaf tersebut. Temuan ini mempunyai implikasi penting terhadap kebijakan institusi zakat dan juga pemerintah Malaysia telah bertekad untuk mengurangi angka kemiskinan Malaysia menjadi 2.8 persen dan mengurangi kemiskinan ekstrim per tahun 2010 berdasarkan Ninth Malaysian Plan.